If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = 7x + 7 Reorder the terms: -3 + 8x = 7x + 7 Reorder the terms: -3 + 8x = 7 + 7x Solving -3 + 8x = 7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -3 + 8x + -7x = 7 + 7x + -7x Combine like terms: 8x + -7x = 1x -3 + 1x = 7 + 7x + -7x Combine like terms: 7x + -7x = 0 -3 + 1x = 7 + 0 -3 + 1x = 7 Add '3' to each side of the equation. -3 + 3 + 1x = 7 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 7 + 3 1x = 7 + 3 Combine like terms: 7 + 3 = 10 1x = 10 Divide each side by '1'. x = 10 Simplifying x = 10
| 5a^2-180=0 | | w-1=3 | | 9.7=x-7.8 | | 4p+3=-6p-5 | | 6x-7=7x-5 | | 9.5x-3=8.5x+3 | | 2x-14=x+8 | | -8m-6=-4 | | -2+y=(-8) | | k-7=-8 | | 6/10+3/5= | | a=1/2(4.5)3 | | 10=(2m+7) | | 12/4=x/2 | | 10(2m+7)= | | 4xy-2xy= | | E=5 | | 2x^2+-6=0 | | t-4=3t-10 | | x+28=4x+4 | | 9d-20=(-20) | | x/4=4/2 | | 4x+(-2)=10 | | (3x+43)=(6x+7) | | -4x-6=10 | | -3x-34=57-10x | | 2d=-2 | | 2+3=(4-1) | | 0.32=x | | 5x-3=8+10 | | 6x-13x-2=10x-24 | | -13+6x=21+4x |